EU Electricity Trade Law: The Legal Tools of Electricity Producers in the Internal Electricity Market - Mäntysaari, Petri (Springer, 2016)
This book aims to describe the mechanisms of the internal wholesale electricity market in terms of the legal tools and practices used by electricity producers, the most important market participants. In this regard, the focus is on Northwestern Europe. Because of the book’s functional perspective, it is not limited to the external regulation of electricity markets at the EU level and also describes the business models and practices employed by electricity producers. Both the physical and financial marketplaces are examined and topics including electricity supply, balancing, transmission and derivatives are covered.